ХОРИЖИЙ ДАВЛАТЛАРДА МАКТАБГАЧА ТАЪЛИМ СИФАТИНИ БОШҚАРИШНИНГ ЎЗИГА ХОС ЖИҲАТЛАРИ - Калмуратов, Т.Н. (SCIENCE and SOCIETY, 2021)
The article analyzes the research work of a number of foreign and local researchers in the field of quality assessment and management of preschool education and the study of the current state of the problem, quality assurance and management of education in public-private partnerships on the basis of legal documents.